Use of chlC-lac fusions to determine regulation of gene chlC in Escherichia coli K-12. - Fimmel, A L (1979)
Gene fusions between the lac structural genes and the chlC locus were isolated, and the regulation of lac gene expression was studied. The fused lac genes were induced by nitrate anaerobically and repressed by the presence of oxygen.